Liszt's transcultural modernism and the Hungarian-gypsy tradition - Loya, Shay (Rochester Boydell & Brewer, 2011)
Some of Franz Liszt's most renowned pieces -- most famously his Hungarian Rhapsodies -- are written in a nineteenth-century Hungarian style known as verbunkos. Closely associated with the virtuosic playing tradition of the Hungarian-Gypsy band, the meaning and uses of this style in Liszt's music have been widely taken for granted and presented as straightforward. Taking a novel transcultural approach to nineteenth-century modernism, Shay Loya presents a series of critiques and sensitive music analyses that demonstrate how the verbunkos idiom, rich and artful in itself, interacted in myriad ways with Liszt's multiple cultural identities, compositional techniques, and modernist aesthetics. Even supposedly familiar works such as the Rhapsodies emerge in a new light, and more startlingly, we find out how the idiom inhabits and shapes works that bear no outward marks of nationality or ethnicity. Particularly surprising is its role in the famously enigmatic compositions of Liszt's old age, such as Nuages gris and Bagatelle sans tonalité. Shay Loya teaches at the University of Durham and is a board member of the Society for Music Analysis (UK).